Ilaj Bil Ghiza (Dieto therapy) in the Prevention and the Treatment of Ailments - Shiffa, M.S.M.; Fahamiya, N. (Faculty of Indigenous Medicine, University of Colombo, 2015)
Ghiza is very vital to any living object as it gives energy and nutrition; therefore it helps the body functions such as growth, mobilization, reproduction and all other Activities...
Keywords: Ghiza; Qoowah; food habit; maaddah-e-marz